In situ, Reversible Gating of a Mechanosensitive Ion Channel through Protein-Lipid Interactions - Dimitrova, Anna; Walko, Martin; Hashemi Shabestari, Maryam; Kumar, Pravin; Huber, Martina; Kocer, Armagan (Frontiers in Physiology, 2016)
Understanding the functioning of ion channels, as well as utilizing their properties for biochemical applications requires control over channel activity. Herein we report a reversible control over the functioning of a mechanosensitive ion channel by interfering with its interaction with the lipid bilayer. The mechanosensitive channel of large conductance from Escherichia coli is reconstituted into liposomes and activated to its different sub-open states by titrating lysophosphatidylcholine (LPC) into the lipid bilayer. Activated channels are closed back by the removal of LPC out of the membrane by bovine serum albumin (BSA). Electron paramagnetic resonance spectra showed the LPC-dose-dependent gradual opening of the channel pore in the form of incrementally increasing spin label mobility and decreasing spin-spin interaction. A method to reversibly open and close mechanosensitive channels to distinct sub-open conformations during their journey from the closed to the fully open state enables detailed structural studies to follow the conformational changes during channel functioning. The ability of BSA to revert the action of LPC opens new perspectives for the functional studies of other membrane proteins that are known to be activated by LPC.